Application of Flywheel Battery in Off-grid Wind Power Generation System - LI Yong; ZHOU Hai-tao; LI Xiao-ying (Gong-kuang zidonghua, 2012)
In allusion to problems of short life, low efficiency of charge and discharge of current energy storage device(battery) in wind power generation system, the paper proposed a schame of taking flywheel battery as the energy storage device, analyzed d-q model and charge and discharge control strategy of flywheel battery. Vector control strategy based on rotor field orientation is adopted in charge control, and the control strategy with DC bus voltage as control object is adopted in discharge control. The simulation results showed that using flywheel battery as energy buffer of off-grid wind power generation system can effectively stabilize the DC bus voltage and improve power quality and stability.